Rise and Fall of Democracy in Regional Government: From Assignment to Election - Hakim, Muhammad Zulfan; Moenta, Andi Pangerang; Jamal, Fazil; Ilmar, Aminuddin; Ilyas, Anshori; Irwansyah, Irwansyah (Yuridika, 2024)
Indonesia has been trying to develop democracy since the early independence. Assignment of the head of the region conducted from 1945 to 1999. After the big reformation in 1999, which started in 2004, Indonesia started a new chapter with the direct election model for regional heads. This research tries to find the philosophy of Indonesia’s choice to select its regional leader according to the law provided. The research is normative research with a conceptual and comparative approach. The results show that the election of regional leaders in Indonesia has not always been in line with the sovereignty of the people and the concept of democracy. Political choice has had a very significant impact. However, as it turns out into practice, as an emerging country in South East Asia, even though an assignment and not by the general election, leaders or regional heads are also considered as democratic as long as it is still on the path of openness, fair game and also according to people’s approval, including if it comes from the regional representative’s choice of candidates.